The discrete nonlinear Schrödinger type hierarchy, its finite dimensional reduction analysis and numerical integrability scheme - Prykarpatsky, A.K.; Cieśliński, J. (Нелінійні коливання, 2017)
We investigate discretizations of the integrable nonlinear Schrodinger dynamical system, well known as the ¨ Ablowitz – Ladik equation, the related symplectic structures and its finite dimensional invariant reductions. An effective scheme of invariant reducing the corresponding infinite system of ordinary differential equations to an equivalent finite system of ordinary differential equations with respect to the evolution parameter is developed. A finite set of recurrent algebraic regular relations, allowing to generate solutions of the discrete nonlinear Schrodinger dynamical system, is constructed, the related functional spaces of ¨ solutions is discussed. Finally, the Fourier transform approach to studying the solution set of the discrete nonlinear Schrodinger dynamical system and its functional-analytical aspects is analyzed. Дослiджуються дискретизацiї iнтегровної нелiнiйної динамiчної системи Шрьодiнгера, вiдомої як рiвняння Абловiца – Ладiка, вiдповiднi симплектичнi структури та її скiнченновимiрнi iнварiантнi редукцiї. Побудовано ефективний алгоритм iнварiантної редукцiї вiдповiдної нескiнченної системи звичайних диференцiальних рiвнянь до еквiвалентної скiнченної системи звичайних диференцiальних рiвнянь вiдносно параметра еволюцiї. Побудовано скiнченну множину рекурентних алгебраїчних регулярних спiввiдношень, що дозволило побудувати розв’язки дискретної нелiнiйної динамiчної системи Шрьодiнгера, та розглянуто вiдповiднi функцiональнi простори розв’язкiв. Проведено аналiз пiдходу перетворення Фур’є до вивчення множини розв’язкiв дискретної нелiнiйної динамiчної системи Шрьодiнгера та її функцiонально-аналiтичних аспектiв.